Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/ajd.12044
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain and tumour necrosis factor-alpha inhibitors in patients with psoriasis

Abstract: Therapy with adalimumab and infliximab is associated with a significant increase in bodyweight and BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 32 publications
6
52
2
2
Order By: Relevance
“…[11][12][13][14] Our study found an association of anti-TNF-α therapy (etanercept, adalimumab and infliximab) with weight gain, and an association of ustekinumab with weight loss; with no statistical significance. With a larger cohort of patients, this association may become statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…[11][12][13][14] Our study found an association of anti-TNF-α therapy (etanercept, adalimumab and infliximab) with weight gain, and an association of ustekinumab with weight loss; with no statistical significance. With a larger cohort of patients, this association may become statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Many studies have evaluated changes in BW or BMI among patients with psoriasis treated with TNF‐α inhibitors . In these reports, the mean increase in BW was 1.5–2.6 kg at 6–7 months after the therapy with TNF‐α inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bodyweight (BW) has been found to influence the response of psoriasis to treatment, including biologic treatment . Recent studies have shown that treatment with tumor necrosis factor (TNF)‐α inhibitors can cause an increase in BW among patients with psoriasis and rheumatoid arthritis (RA) . However, limited information is available in terms of the effects of interleukin (IL)‐23 and IL‐17A inhibitors on BW in patients with psoriasis .…”
Section: Introductionmentioning
confidence: 99%
“…This evidence may, at least partially, give reason of (i) the enhanced TNF-α levels detected in obese subjects, with putative protective function; (ii) the body weight increase observed in psoriatic patients undergoing treatment with TNF-α inhibitors or other antipsoriatic agents decreasing TNF-α expression levels [56,[70][71][72]. However, data on TNF-α role in increased adiposity are controversial as it may also contribute to obesity counteracting insulin receptor activity and inhibiting glucose transporter (GLUT)-4, with a consequent enhancement of insulin levels that stimulates the hunger center [68].…”
Section: Tnf-αmentioning
confidence: 99%